Social intelligence as moderator in the relation between narcissism and aggression in at‐risk adolescents. Issue 2 (13th November 2022) - Kim, Hyunah; Barry, Christopher T.
Abstract: This study examined the moderating role of social intelligence (SI) in the associations of grandiose and vulnerable narcissism (VN) with peer‐reported overt and relational aggression (RA). The sample consisted of 286 adolescents aged 15 to 19 recruited from a residential program for youth who have dropped out of school. Results showed that whereas grandiose narcissism (GN) was related to both forms of aggression, VN was related to neither overt nor RA. However, SI moderated the relation between VN and both forms of aggression such that SI works as either a risk or protective factor for adolescents with higher levels of narcissism depending on the subdimensions of SI and aggression. The findings indicate that SI may play a role in how adolescent peers perceive the behavior of relatively narcissistic individuals.